Pyrodinium bahamense var. compressum and other dinoflagellate cyst distribution in surface sediments of Villareal Bay, Samar, Philippines - Villamor, Nichole Jane Z. (2017)
This study provided a baseline assessment of the abundance and distribution of dinoflagellate cysts present in the surface sediments of Villareal Bay, Samar, Philippines. Surface sediments were collected from 10 stations using a grab sampler on January 2017. Sediment samples collected were physicochemically characterized and palynological technique was used for cyst processing. A total of 30 species of diniflagellate cysts were identified and belonged to 6 taxonomic groups: Calciodineloid, Gonyaulacoid, Gymnodinoid, Tuberculodinoid, Diplosalid and Protoperdinoid. Cysts were present in all stations and cyst density values ranged from 7-30 cysts g raise to negative 1 DW. The harmful species Scrippsiella trochoidea was found to be dominant in 3 stations. Pyrodinium bahamense var. compressum found in 6 stations had low cyst counts with values ranging from 1-4 cysts g raise to negative 1 DW. Cyst concentrations may have been affected by sedimentological and environmental factors such as substrate type, organic matter content, nutrient concentrations, and depth.